Macroeconomic policy regimes in Western industrial countries - Herr, Hansjörg, 1951- (Routledge, 2010)
Macroeconomic Policy Regimes in Western Industrial Countries explains how certain countries have created a more liberal and market-based type of capitalism. The emphasis throughout is on how understanding macroeconomic policies, and the institutional framework in which they operate, is vital to understanding the long-run dynamics of a capitalist economy.